Application of a regularised Coulomb sliding law to Jakobshavn Isbræ, West Greenland - Trevers, Matt; Payne, Antony J.; Cornford, Stephen L. (Copernicus Publications, 2024)
Reliable projections of future sea level rise from the polar ice sheets depend on the ability of ice sheet models to accurately reproduce flow dynamics in an evolving ice sheet system. Ice sheet models are sensitive to the choice of basal sliding law, which remains a significant source of uncertainty. In this study we apply a range sliding laws to a hindcast model of Jakobshavn Isbræ, West Greenland from 2009 to 2018. We show that commonly used Weertman-like sliding laws can not reproduce the large seasonal and inter-annual variations in flow speed, while the assimilation of regular velocity observations into the model improves the model accuracy. We demonstrate that a regularised Coulomb friction law, in which basal traction has an upper limit, was able to reproduce the peak flow speeds most accurately. Finally we find evidence that the speed at which sliding transitions between power-law and Coulomb regimes may vary spatially and temporally. These results point towards the possible form of an ideal sliding law for accurately modelling fast-flowing glaciers and ice streams.